STRENGTH AND DURABILITY EFFECT ON STABILIZED SUBGRADE SOIL - Noraida, Razali; Norazzlina, M.Sa'don; Abdul Razak, Abdul Karim (UNIMAS Publisher, 2022)
This paper presents the development of strength and durability effect of stabilized soil. The clayey soil collected from Kota Samarahan, Sarawak was admixed with cement, fly ash and rubberchip as an additive for stabilization purposes. The optimum mixture determined was then used as a recommendation for the design guidelines of subgrade based on JKR Standard Specification for Road Works. The stabilized clay specimens were prepared with 5% cement and various fly ash and rubber chips contents, of 5%, 10% and 15%, respectively. The specimens were then cured for 7 and 28 days before subjected to Unconfined Compressive Strength (UCS) tests and California Bearing Ratio (CBR) tests. As observed, the stabilization improved the strength and stiffness of the soil properties significantly. However, the addition of 15% rubberchip shows a reduction in strength for both 7 and 28 days curing period. From the study, the optimum mixture, which fulfilled the JKR Standard Specification was the mixture of 5% cement and 15% fly ash. However, the mixture of 5% cement and 10% rubberchip is also recommended to be used as an alternative to stabilize the subgrade for low volume road.